Study of Serum Uric Acid level in Primary Hypothyroid Patients - المنصور, رنا; ربا سلمان ,; إبراهيم سليمان, (Latakia University Journal -Medical Sciences Series, 2022)
BACKGROUND: Hypothyroidism is one of themost common endocrinal disorders. Thyroid hormones influence uric acid levels. The relationship between UA levels and thyroid dysfunctions has been investigated in several studies which provided conflicting results. THE AIM: To evaluate the effect of hypothyroidism on serum Uric Acid level. MATERIALS AND METHODS: A case control study was performed and included 245 individuals who attended the Endocrinology & Metabolic Diseases clinic in Tishreen University Hospital in Lattakia between 2020 and 2021 (167 Hypothyroid patients and 78 normal controls). Serum TSH, FT4, FT3 levels were evaluated to determine theprimary hypothyroid patients. UA was evaluated along with other necessary parameters in all individuals participating in the study. Hypothyroidism was defined according to the TSH value (TSH>4.31µlU/L), and was classified into clinical (overt) hypothyroidism if FT4<0.82 ng/dL (n=82), and subclinical hypothyroidism if FT4 was normal (n=85). Normal UA range was determined as 2.4–6.0 mg/dL in women and 3.4–7.0 mg/dL in men. RESULTS: Serum Uric acid was significantly elevated in primary hypothyroid groups as compared to euthyroid controls, (p=0.0001). CONCLUSION: Mean serum uric acid levels was significantly higher in hypothyroid patients compared to controls. These findings suggest that hyperuricemia is associated with primary hypothyroidism. Thus, uric acid should be regularly monitored in hypothyroid patients.